Democracia participativa e regulação econômica: uma questão de legitimidade - Duarte Júnior, Ricardo César Ferreira (2013)
This work presents an analysis about the legitimation of independent regulatory commission`s rulemaking power by participation procedure. It is observed that political and administrative decentralization and fragmentation of State, with the purpose of approaching citizens and provide, more efficiently, the functions acquired by the passage of the Welfare State, leads to a deficit of legitimacy (democratic crisis), which is noticeable in the making of legal norms by directors of independent regulatory commission to regulate specific economic sector. However, we understand that this crisis stems from the observation of the contemporary world from dogmas and legal institutions of the eighteenth century, without their evolution and adaptation to the modern world. The legitimacy must be perceived as the justification of power, relation command /obedience, which, from the Modern State, has the democracy as standard. Therefore, just as the world has evolved and demanded political and administrative decentralization to accompany him, it is necessary to the development of the idea of representative democracy (formal legitimacy) to participatory democracy (legitimacy stuff). Legitimacy is not confused with the legality: as the legality is on observance to internal legal system, the "rules of play"; legitimacy, as inputs to be fed into this system, the selection of the different expectations in the environment. Nevertheless, the legitimacy will take place by legality, through introduction of rational and communicative procedures: procedures get fundamental importance because these will be the means to select the expectations to be introduced in the legal system in order to make decisions more fair, rational and qualified towards society. Thus, it is necessary to its opening to the environment for dialogue with the government. In this context, we try to make an analysis of constitutional norms based on systematic and teleological interpretation of these norms to build these arguments. According to the Constitution of 1988, participatory democracy is a result of the democratic principle (sole paragraph of art. 1 of the Constitution), and it is an expression of citizenship and political pluralism, both foundations of Republic (respectively Art. 1st, inc . V and II of the Constitution), as well as the national consciousness. From another point of view, that principle consists of an evolution in the management public affairs (principle of Republic). The right of interested participate in the rulemaking process derives both the principle of popular participation (part of the democratic principle) and the republican principle as the due process constitutional (art. 5, LIV and LV, CF/88) and the right to petition (Art . 5 °, inc. XXXIV, "a", CF/88), and it is the duty of the State not only be open to participation and encourage it. Ignoring stakeholder involvement in procedures and / or expressions compiled can be causes of invalidation of the rule of law produced by addiction of procedure, motive, motivation and/or because of the administrative act. Finally, we conclude that the involvement of stakeholders in the process of making rules within the independent regulatory commission is the legitimacy and the validity of rules; and that, despite of the expressions do not bind the decision making, they will enter the system as juridical fact, balancing the field of technical discretionary of agencies